Study on Ex-Corruption Convicts Become Legislative Candidates - Ahmad Sobari (Budapest International Research and Critics University, 2022)
This study discusses the prohibition of former corruption convicts from being candidates for legislative members, regulated in the General Election Commission Regulation Number 20 of 2018. However, the ban was overturned by the Supreme Court because it limited a person's political rights. This paper uses normative juridical research using a statutory approach, the legal materials: primary, secondary, tertiary, with library data collection techniques. The hypothesis is that the Supreme Court, in cancelling this decision, only pays attention to procedural matters without considering the principle of benefit and partiality to the people. This study also discusses the reasons and considerations of the Supreme Court in cancelling the ban on ex-corruption convicts from becoming legislative candidates that the General Elections Commission has formed with the spirit of creating elections with integrity.